2020
DOI: 10.1186/s40246-020-00267-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vulnerability: the potential impact of genetic susceptibility and airborne transmission

Abstract: The recent coronavirus disease , caused by SARS-CoV-2, is inarguably the most challenging coronavirus outbreak relative to the previous outbreaks involving SARS-CoV and MERS-CoV. With the number of COVID-19 cases now exceeding 2 million worldwide, it is apparent that (i) transmission of SARS-CoV-2 is very high and (ii) there are large variations in disease severity, one component of which may be genetic variability in the response to the virus. Controlling current rates of infection and combating future waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 56 publications
2
107
0
11
Order By: Relevance
“…routes [8], although some recent studies suggest that airborne transmission might also be possible [9][10]. The incubation period typically ranges between 2 and 14 days, although longer incubation times have been also reported [11].…”
Section: Covid-19 Is Primarily Transmitted Between People Through Resmentioning
confidence: 99%
“…routes [8], although some recent studies suggest that airborne transmission might also be possible [9][10]. The incubation period typically ranges between 2 and 14 days, although longer incubation times have been also reported [11].…”
Section: Covid-19 Is Primarily Transmitted Between People Through Resmentioning
confidence: 99%
“…Moreover, advanced age, male sex and preexisting conditions such as cardiovascular, pulmonary, and renal diseases make a subject more vulnerable to the more severe health consequences of COVID-19 [ 17 , 18 ].…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%
“…(2) Diagnostic variability: Although there may be a negative diagnosis after repeated tests, it may become positive unexpectedly [ 8 ]. (3) Multiple transmission routes: It is mainly transmitted through droplets or direct contact, but some studies have even found that it can be transmitted by air [ 9 , 10 , 11 , 12 ], feces [ 13 , 14 , 15 ], and asymptomatic carriers [ 16 , 17 , 18 ]. Moreover, its basic reproductive number (R0) has been determined to range between 2–3 2 , and the spreading region is probably wide enough to trigger a pandemic [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its basic reproductive number (R0) has been determined to range between 2–3 2 , and the spreading region is probably wide enough to trigger a pandemic [ 19 ]. (4) Genome mutation possibility: The mutation of the viral RNA genome is possible [ 12 , 19 ]; hence, the research and development of vaccines and drugs are great challenges. Even if the discovery is successful and products are approved for marketing, the effective period of the vaccine products and approved drugs may be limited due to mutation and resistance.…”
Section: Introductionmentioning
confidence: 99%